2022
DOI: 10.1177/19322968221093362
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Study of the Inflammatory Tissue Response Surrounding a Novel Extended-Wear Kink-Resistant Insulin Infusion Set Prototype Compared With a Commercial Control Over Two Weeks of Wear Time

Abstract: Background: Infusion set function remains the limiting factor of insulin pump therapy due to nonmetabolic complications. Here, we tested an investigational extended-wear infusion set prototype with a soft, angled, wire-reinforced cannula with three additional side holes, and compared failure mechanisms and tissue response with a commercial Teflon control. Methods: A total of 48 Teflon and 48 prototype infusion sets were inserted subcutaneously every other day for 14 days in 12 swine and infused with dilute ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Investigations in swine have shown that angled infusion sets at 35° may result in less-severe inflammatory reactions than perpendicular sets. 53,54 Reports show that Teflon may result in less inflammation than steel in swine 55,56 although an earlier study reported minimal differences in keeping with data reported in humans. 57 A metaanalysis of such results warrants a dedicated systematic review.…”
Section: Discussionmentioning
confidence: 90%
“…Investigations in swine have shown that angled infusion sets at 35° may result in less-severe inflammatory reactions than perpendicular sets. 53,54 Reports show that Teflon may result in less inflammation than steel in swine 55,56 although an earlier study reported minimal differences in keeping with data reported in humans. 57 A metaanalysis of such results warrants a dedicated systematic review.…”
Section: Discussionmentioning
confidence: 90%
“…The prototype investigational Capillary Biomedical (Irvine, CA, USA) extended‐wear IIS (CBX IIS) contains a coil‐reinforced soft polymer (nylon‐derivative) indwelling cannula with one distal and three proximal ports (Figure 1A). This novel cannula has shown significantly improved immunological tolerability in pre‐clinical swine studies 16 . Each infusion set has two basic components: the infusion set body with an indwelling, angled cannula, and a tubing connector to the infusion pump reservoir (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…Novel seven-day infusion sets may lead to fewer cases of LH, but studies are underway to quantify this hypothesis. 26,27 Additives in different types of insulin may also have some influence because of the introduction of foreign bodies that can activate the immune system. Insulin delivery via jet injectors has been speculated to decrease LH risk.…”
Section: Skin Complications Of Diabetesmentioning
confidence: 99%